Public Health in Big Cities: Looking Back, Looking Forward. (January 2015) - Fielding, Jonathan E.
Abstract : This commentary provides reflections of a public health official on the important role public health departments play in advancing the goals of the larger public health enterprise in big cities, counties, and large metropolitan areas.